Integrated diagenetic, structural and paleomagnetic study of remagnetized folded Mississippian-Triassic units from the Southern Canadian Cordillera, Alberta and British Columbia - (:unkn) unknown (My University, 2010)
Determining the timing and origin of fluid-related diagenetic events relative to orogenesis is crucial for understanding the interaction between orogenesis and diagenesis. Two folds in Mississippian carbonates (Line Creek anticline and Mt. Kidd anticline/syncline) and one fold in Pennsylvanian-Triassic units (Kent anticline) was investigated in the Southern Canadian Cordillera to test for a link between fluid flow, hydrocarbon migration/alteration and the formation of a multi-component remagnetization. This issue was investigated using an integrated diagenetic, structural and paleomagnetic approach. Geochemical, petrographic and fluid inclusion analysis was used to determine the nature of the diagenetic events while combined rock magnetic and paleomagnetic analysis was used to determine the magnetic carriers and age of both a high temperature and intermediate temperature chemical remanent magnetization (HTCRM and ITCRM, respectively). The timing of the HTCRM, contained in magnetite, is Early Cretaceous (~Aptian) and pre-tilting at Line Creek, although is inconclusive at Mt. Kidd due to its syn-tilting nature. The ITCRM is post tilting and Late Tertiary at Mt. Kidd, although is inconclusive at Line Creek due to its syn-tilting result A bedding parallel vein contact test shows direct correlation to the total component magnetic intensity of the HTCRM while a tectonic vein contact test shows a correlation to the total component intensity of the ITCRM. Elevated 87Sr /86Sr data indicates that the rocks have been altered by radiogenic fluids. C/O isotopes show evidence for a wide range warm fluids which is confirmed by fluid inclusion homogenization temperatures (149-212°C). The geochemical and petrographic results are consistent with the interpretation that the HTCRM formed as a result of a regional migration of hydrocarbons and/or evolved basinal fluids. The ITCRM is interpreted to be the result of thermal sulfate reduction (TSR), caused by alteration of hydrocarbons, based on the observation of multiple by-products of TSR.

Because of the possibility of structural complications the conventional tilt test results where integrated with small circle intersection analysis (SCI) and calcite twin strain analysis. The Line Creek anticline formed during low to moderate burial, low deviatoric strain, kink folding, brittle deformation and contained no structural complications leading to a reliable age determination. On the other hand the Mt. Kidd anticline-syncline pair formed under higher burial temperatures, higher deviatoric strain and ductile deformation leading to structural complications affecting the HTCRM. These structural complications led to erroneous age determinations and required a modification of the HTCRM data set, based on the SCI results. This modification cleared up some deformation related discrepancies allowing for the determination that the early syn-tilting remagnetization at Mt. Kidd can be attributed to either strain modification or spurious rotations of a pre-tilting HTCRM. The ITCRM is a late syn-tilting to post tilting Tertiary remagnetization contained in pyrrhotite and has been determined to not have been affected by any structural complications.
Keywords: Diagenesis--American Cordillera; Paleomagnetism--American Cordillera; Orogeny--American Cordillera; Folds (Geology)